Effect of halogen on imprinting gradient refractive index microstructure in GeS2–Ga2S3–NaX (X=F, Cl, Br, I) glasses for broadband infrared diffraction gratings. Issue 20 (15th October 2021) - Yang, Guang; Yang, Chuanfan; Hu, Daming; Peng, Changzhe; Tang, Ke; Lu, Yunjun; Tang, Feng; He, Xiaoyan; Xu, Yinsheng
Abstract: Chalcohalide glasses with a gradient refractive index (GRIN) microstructure were imprinted by microthermal poling for realizing diffractive optical elements covering the visible to middle-infrared wavelength range. The effect of halogen ions on the saturation poling voltage (U), surface profile, diffraction pattern, optical transmittance, GRIN microstructure, and structural rearrangement of poled glass is investigated. An effective imprinting formation region for a GRIN microstructure based on the U and glass composition is observed under fixed poling time and temperature. The onset U (60 V–150 V) and activation energy of mobile cations (0.449 eV–0.533 eV) decreases with the atomic number of the halogen from F to I, but the saturation diffractive order (8th to 11th levels) and phase difference (~0.08λ to 0.18λ) increases accordingly. The onset U and activation energy decrease with the deformability of the glass network and radius of the halogen ions. The phase difference and saturation diffractive orders decrease with the proportion and electronegativity of interval halogen atoms in the glass network. Thus, chalcohalide glasses with GRIN microstructures can be tailored by adjusting the type of halogen ions for realizing various diffraction optical elements.